Analisis Data Sistem Informasi Geografis Rumah Tidak Layak Huni (RTLH) Menggunakan Metode Fuzzy Logic - Khairil Hamdi (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Houses and other types of housing are things that cannot be separated from the needs of human life. The house function as a place to refuge, a place to live, and to gather with family. Proper housing is the basic need of all people who will strengthen the family, as the main pillar of the nation's strength, at the same time acting as a bastion against various health risks. The properness of a house for family housing becomes the basis for the growth and development of a better family life. Roofs, floors, and walls (aladin) are indicator data of whether a house is proper or not at the time of the survey. An adaptive, flexible and interactive computer-based system is used to solve unstructured problems so the more valuable decisions can be produced. This study describes how to process data using fuzzy logic methods. The expected result is to support the decision whether or not a house is feasible are in accordance with the facts and location data in the field. To determine which housing are categorized as severely damaged, moderate and lightly damaged by using the fuzzy logica method with roof, floor and wall variables as input variables so that local governments will find it easier to sort work priorities in the short, medium and long term